ASSESSMENT OF GOMBE GOES GREEN (3G): A MITIGATION STRATEGY FOR CLIMATE CHANGE CONTROL IN GOMBE STATE, NIGERIA - Yusuf, I. K.; Abdullahi, I.M.; Abdullahi, S. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study examined the assessment of the Gombe Goes Green (3G): A mitigation strategy for climate change control in Gombe State, Nigeria. A multi-stage sampling technique was used to select 201 respondents; Data were collected through the administration of structured questionnaires and analyzed using descriptive and inferential statistics. The results revealed that 31.3% of the respondents fell within the age range of 30–39 years, with a mean age of 38 years. Majority (65.7% and 62.7%) were married and male, and 33.8% had attained secondary education. The average household size was 6 members. The results further showed that the respondents had the mean of 11 years in farming experience. The findings further revealed that 58.7% of the respondent belonged to one form of association, and 54.2% had access to extension services while access to credit/funding was relatively low (36.3%). The result revealed that age, farming experience, access to funding and farm size were significant at P<0.05, access to extension services, participation in government programs, use of agroforestry are significant at P<0.01 while educational level and membership in association, were also positive and significant at P<0.001. The major constraints in sustaining the 3G project were destruction of trees, inadequate funding, lack of community participation, poor monitoring and inadequate awarenesses. The study concluded that the Gombe Goes Green initiative has a significant impact on climate change mitigation and community development in the study area. Based on these results, it was recommended that, community participation be encouraged, government and development partners strengthen follow-up mechanisms, increase funding and sensitization campaigns to ensure the sustainability of environmental initiatives.